Profiling of formaldehyde, glyoxal, methylglyoxal, and CO over the Amazon: normalized excess mixing ratios and related emission factors in biomass burning plumes - Kluge, Flora; Hüneke, Tilman; Knecht, Matthias; Lichtenstern, Michael; Rotermund, Meike; Schlager, Hans; Weyland, Benjamin; Pfeilsticker, Klaus (Atmospheric chemistry and physics, 2020)
Abstract. We report on airborne measurements of tropospheric mixing ratios and vertical profiles of formaldehyde (CH2O), glyoxal (C2H2O2), methylglyoxal and higher carbonyls (C3H4<msubsup>O2*</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="41pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="af988864cbcdcafdc3df86b6a358936b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-12363-2020-ie00001.svg" width="41pt" height="14pt" src="acp-20-12363-2020-ie00001.png"/></svg:svg>) (see below), and carbon monoxide (CO) over the Amazon Basin during the ACRIDICON-CHUVA campaign from the German High Altitude and Long-range research aircraft (HALO) in autumn 2014. The joint observation of in situ CO and remotely measured CH2O, C2H2O2, and C3H4<msubsup>O2*</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="41pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ef1d34cc9d4b75383356dfc5a6d1cdf1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-12363-2020-ie00002.svg" width="41pt" height="14pt" src="acp-20-12363-2020-ie00002.png"/></svg:svg>, together with visible imagery and air mass back-trajectory modelling using NOAA HYSPLIT (National Oceanic Atmospheric Administration, HYbrid Single-Particle Lagrangian Integrated Trajectory), allows us to discriminate between the probing of background tropical air, in which the concentration of the measured species results from the oxidation of biogenically emitted volatile organic compounds (VOCs, mostly isoprene), and measurements of moderately to strongly polluted air masses affected by biomass burning emissions or the city plume of Manaus. For 12 near-surface measurements of fresh biomass burning plumes, normalized excess mixing ratios of C2H2O2 and C3H4<msubsup>O2*</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="41pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="2ed961b4f0644d9e3f0f6f3d6a5f4cd1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-12363-2020-ie00003.svg" width="41pt" height="14pt" src="acp-20-12363-2020-ie00003.png"/></svg:svg> with respect to CH2O are inferred and compared to recent studies. The mean glyoxal-to-formaldehyde ratio RGF=0.07 (range 0.02-0.11) is in good agreement with recent reports which suggest RGF to be significantly lower than previously assumed in global chemical transport models (CTMs). The mean methylglyoxal-to-formaldehyde ratio RMF=0.98 (range 0.09-1.50) varies significantly during the different observational settings but overall appears to be much larger (up to a factor of 5) than previous reports suggest even when applying a correction factor of 2.0±0.5 to account for the additional dicarbonyls included in the C3H4<msubsup>O2*</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="41pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="49b151acafa38023d601c2a77f7be38e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-12363-2020-ie00004.svg" width="41pt" height="14pt" src="acp-20-12363-2020-ie00004.png"/></svg:svg> measurements. Using recently reported emission factors of CH2O for tropical forests, our observations suggest emission factors of EFG=0.25 (range 0.11 to 0.52) g kg−1 for C2H2O2 and EFM = 4.7 (range 0.5 to 8.64) g kg−1 for C3H4<msubsup>O2*</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="41pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9b23584d462cefbaaa486b5b3c5dfaa8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-12363-2020-ie00005.svg" width="41pt" height="14pt" src="acp-20-12363-2020-ie00005.png"/></svg:svg>. While EFG agrees well with recent reports, EFM is (like RMF) slightly larger than reported in other studies, presumably due to the different plume ages or fuels studied. Our observations of these critical carbonyls and intermediate oxidation products may support future photochemical modelling of air pollution over tropical vegetation, as well as validate past and present space-borne observations of the respective species.